Development of Video-Based Contextual Teaching Materials on Social Harmony Material at SMAN 3 Semarang - Farha, Fina Nayla; Atmaja, Hamdan Tri; Brata, Nugroho Trisnu (Journal of Educational Social Studies, 2025)
This study aims to identify the use of social harmony teaching materials at SMAN 3 Semarang and measure student responses to developing video-based teaching materials as a solution to the limitations of existing teaching materials. This study uses the R&D (Research and Development) method. The results of the study indicate that the teaching materials used are dominated by text, such as textbooks, teaching modules, PPT, and LKPD, which provide theoretical conceptual understanding but are less relevant to the local socio-cultural context of students. The lack of integration of visual and interactive media makes learning monotonous, so that motivation and involvement in the learning process decrease. To overcome these problems, video-based teaching materials were developed that present visual illustrations, animations, and examples of local phenomena that are close to students' lives. In addition, the development of videos shows a positive response from most students. The development of video-based teaching materials has been proven to be able to create a more meaningful, interesting learning experience and encourage students to internalize the values ​​of social harmony in their lives.